ESTUDIOS SOBRE LA MEDULA OSEA VII DATOS NUMERICOS DEL MIELOGRAMA DE LA RATA BLANCA DIMENSIONES DE LOS ERITROBLASTOS - GONZALEZ GUZMAN, IGNACIO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1947)
The internal angle of derivation of a bipolar lead is defined as that subtended at the center of gravity of the heart by the interelectrodal line It is shown that the apparent value of the cardiac vector in such leads (those of Sulzer and Duchosal, in pa
BOL MEN BAN REF JAL
Keywords: ESTUDIOS, MEDULA OSEA, DATOS NUMERICOS, MIELOGRAMA, RATA BLANCA, DIMENSIONES, ERITROBLASTOS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL